2019
DOI: 10.3390/vision3040051
|View full text |Cite
|
Sign up to set email alerts
|

Rivalry Onset in and around the Fovea: The Role of Visual Field Location and Eye Dominance on Perceptual Dominance Bias

Abstract: When dissimilar images are presented to each eye, the images will alternate every few seconds in a phenomenon known as binocular rivalry. Recent research has found evidence of a bias towards one image at the initial ‘onset’ period of rivalry that varies across the peripheral visual field. To determine the role that visual field location plays in and around the fovea at onset, trained observers were presented small orthogonal achromatic grating patches at various locations across the central 3° of visual space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Figure 2 shows no effect of any invention on the time to first switch, whereas the patching intervention clearly shifted dominance toward the patched eye during sustained rivalry (Figure 4). Although research continues to highlight the idiosyncratic nature of onset rivalry, the current results are consistent with previous studies emphasizing the role of eye dominance, luminance, and color in determining onset dominance compared with higher level factors (Dieter, Sy, & Blake, 2017;Stanley, Forte, & Carter, 2019;. As the occlusion procedure involved a translucent patch that degraded form perception but largely preserved luminance and color, the occlusion procedure may have spared the neural signaling processes that are most relevant to the period of onset rivalry.…”
Section: Discussionsupporting
confidence: 89%
“…Figure 2 shows no effect of any invention on the time to first switch, whereas the patching intervention clearly shifted dominance toward the patched eye during sustained rivalry (Figure 4). Although research continues to highlight the idiosyncratic nature of onset rivalry, the current results are consistent with previous studies emphasizing the role of eye dominance, luminance, and color in determining onset dominance compared with higher level factors (Dieter, Sy, & Blake, 2017;Stanley, Forte, & Carter, 2019;. As the occlusion procedure involved a translucent patch that degraded form perception but largely preserved luminance and color, the occlusion procedure may have spared the neural signaling processes that are most relevant to the period of onset rivalry.…”
Section: Discussionsupporting
confidence: 89%
“…Considering first the research most comparable to our work here (i.e., investigating the nasotemporal asymmetry in IOC), we find little consensus in the handful of studies dedicated to this line of investigation. Whereas some studies show an advantage for the nasal VHF 25 27 , other studies showed either no, mixed, or even opposite results regarding the dominance of nasally versus temporally presented stimuli in IOC 28 30 , 41 , 42 . Regardless, the current study provides decisive results as we show a robust advantage for the nasal VHF during IOC evoked by b-CFS, across 300 + observers in five independent datasets.…”
Section: Discussionmentioning
confidence: 93%
“…raise the question whether interocular competitive strength is also dependent on the VHF to which the competing stimuli are presented. Not many studies examined VHF asymmetries in IOC, and the studies which have, have provided conflicting results: some studies reported an enhanced performance for stimuli in nasal VHF locations 25 27 while others suggested little effect of VHF location or even an advantage for stimuli in temporal VHF locations 28 30 . The studies that observed VHF asymmetries in IOC (in either direction) do not elaborate much on potential explanations for the VHF asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…We weighted the differences as it is well possible for individual tract/radiation differences to scale with overall tissue properties. Finally, we elected to take the “absolute” asymmetries, as the signage of the perceptual manifestation of SED is not intuitive, especially as it relates to physiological asymmetries ( Dieter and Blake, 2015 ; Stanley et al, 2019 ). We arrive at a metric of the OR then, that allows us to gauge correlates of the degree of eye dominance.…”
Section: Methodsmentioning
confidence: 99%